Changes in Abdominal Circumference during Endurance Exercise: A Pilot Study. (June 2014) - Spooner, H; Schott II, H; Nielsen, B; O′Connor‐Robison, C; Harris, P
Abstract : Introduction: Horses have a large intestinal reserve of water and electrolytes that can be absorbed to replace sweat fluid losses during endurance exercise. As a consequence, the abdomen develops a "tucked‐up" appearance; however, data documenting changes in abdominal circumference during endurance exercise are lacking. Methods: Abdominal circumference was measured directly (in triplicate with a measurement tape to nearest cm) every 15‐km at three sites (front, middle, and back) in six 2‐year‐old Arabian horses that completed four 60‐km bouts of treadmill exercise. Data were analyzed by repeated measures ANOVA and compared to body weight (BW) loss by correlation analysis. Results: Abdominal circumference decreased at all three sites during the exercise test (1.8 ± 0.7, 1.4 ± 0.7, and 3.1 ± 1.3 cm for front, middle, and back, respectively, [representing 1–2% of total circumference]) with the greatest decrease (>50% of total) occurring during the initial 15‐km of the exercise test. Changes in abdominal circumference during each step of the exercise test were significantly correlated with BW changes (R values 0.18–0.39, P<0.05 for all). Conclusions: These data support the clinical observation that the abdomen decreases in size during endurance exercise and that the largest changes are observed in the earlier stages of exercise, similar to the initial greater decrease in BW that has been documented in several studies during the initial half of endurance competitions. Ethical Animal Research: This study was approved by the Animal Use Committee of Michigan State University.Sources of funding: WALTHAM Centre for Pet Nutrition.Competing interests: none.